Exercise intensity classification in cancer patients undergoing allogeneic HCT - Kühl, Rea; Rosenberger, Friederike; Schommer, Kai; Schmidt, Martina; Dreger, Peter; Huber, Gerhard; Bohus, Martin; Ulrich, Cornelia; Wiskemann, Joachim (Medicine and science in sports and exercise, 2015)
Exercise intervention studies during and after cancer treatment show beneficial effects for various physical and psychosocial outcomes. Current exercise intensity guidelines for cancer patients are rather general and have been adapted from American College of Sports Medicine (ACSM) recommendations for healthy individuals. Intensive cancer treatment regimens such as allogeneic hematopoietic stem cell transplantation (allo-HCT) may change the cardiovascular response to acute exercise. Therefore, we evaluated the relationships between %V˙O2 reserve (%V˙O2R, reference) and %HRR, %HRmax, and %V˙O2max and compared calculated intensities with given intensities by ACSM. Measurements before and 180 d after allo-HCT from a randomized controlled trial were used. Only patients who reached maximal effort and at least two exercise stages in our maximal incremental cycling test were included. Before allo-HCT, 106 patients were included, and 180 d after treatment, 49 patients met our inclusion criteria. Individual regression lines were calculated with V˙O2R as the reference. Calculated exercise intensities for endurance training prescription were compared with ACSM values. Before allo-HCT, %HRR values of patients were significantly lower than ACSM values, and %HRmax and %V˙O2max values were significantly higher (except 90% HRmax, which was significantly lower, all P < 0.01). One hundred eighty days after allo-HCT, values for %HRR were not significantly different to ACSM values (except 90%, which was significantly lower, P = 0.01), whereas %HRmax and %V˙O2max were significantly higher (all P < 0.05). Furthermore, regression models revealed no influence of beta-blockers on calculated intensities. ACSM’s exercise intensity recommendations for endurance training may not be applicable for cancer patients during and 180 d after allo-HCT because they may not meet the targeted intensity class, with the exception of %HRR 180 d after allo-HCT.